Constitutional Convention in the National Legal System in Indonesia - Lorenzo K.E de Fretes; Lydia Anindira; Michelle Sharon Anastasia (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The Constitutional Convention is defined as an unwritten rule that arises or arises as a result of a State custom with the aim of achieving statutory indications. The State of Indonesia is a country that adheres to Civil Law rules which of course this rarely happens, but the Convention itself is important for the State of Indonesia and should not disappear from life in this country. This article attempts to explore the need for Conventions within countries and how to prevent them from disappearing quickly. This article carries out normative research methods that prioritize legal theory and systematics.